Accuracy of computer programs in predicting orthognathic surgery soft tissue response. - Kaipatur NR; Flores-Mir C (Journal of Oral & Maxillofacial Surgery (02782391), 2009)
PURPOSE: The aim of the present systematic review is to investigate the accuracy of computer programs in predicting soft tissue response subsequent to skeletal changes after orthognathic surgery. MATERIALS AND METHODS: A systematic computerized database search was conducted using Ovid Medline, Ovid Medline in-process and other nonindexed citations, all EBM reviews (including Cochrane DSR, ACP Journal, DARE, CCTR), Embase Experta Medica, Pascal, and Thomsen's ISI Web of Science databases. The terms orthognathic surgery, orthodontic treatment, computer prediction, computer simulation, growth prediction, accuracy, precision, forecast, and human studies were used for the searches. The reference lists of all the selected articles were also searched for any potential articles that might have been missed in the electronic search of the database, and additional information not available through the articles was obtained directly from the source (by contacting the author). RESULTS: Out of the 40 initially identified articles only 7 articles fulfilled the final selection criteria. All 7 studies in general showed accurate prediction outcomes (less than 2 mm) when compared with actual results in both horizontal and vertical directions. From all the available computer prediction programs Quick Ceph, DentoFacial Planner (DFP), and Computer-Assisted Simulation System for Orthognathic Surgery (CASSOS) were the most frequently used. CONCLUSIONS: The most significant area of error in prediction through the available computer prediction programs was the lower lip area. Although the individual errors are almost always minimal (less than 2 mm), the composite addition of these minimal errors could have clinical implications. Copyright © 2009 by the American Association of Oral and Maxillofacial Surgeons.